2023
DOI: 10.1039/d3fo02177g
|View full text |Cite
|
Sign up to set email alerts
|

Black chokeberry (Aronia melanocarpa L.) polyphenols attenuate obesity-induced colonic inflammation by regulating gut microbiota and the TLR4/NF-κB signaling pathway in high fat diet-fed rats

Yue Zhu,
Peng-ju Cai,
Han-chu Dai
et al.

Abstract: This study investigated the potential benefits of black chokeberry polyphenols (BCPs) supplementation on lipopolysaccharide (LPS)-stimulated inflammatory response in RAW264.7 cells and obesity-induced colonic inflammation in high-fat diet (HFD)-fed rats model....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…The expression of tight junction proteins such as ZO-1, Occludin and Claudin1, resulting in increased intestinal barrier permeability and elevated blood LPS levels. LPS can activate the TLR4/MyD88/NF- κ B pathway to trigger TNF- α , MCP-1 and IL-6 release (L. Shi et al, 2022 ; Zhu et al, 2023 ). The increasing serum LPS, TNF- α , MCP-1 and IL-6 levels mean the low-grade systemic inflammation in MetS rats.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of tight junction proteins such as ZO-1, Occludin and Claudin1, resulting in increased intestinal barrier permeability and elevated blood LPS levels. LPS can activate the TLR4/MyD88/NF- κ B pathway to trigger TNF- α , MCP-1 and IL-6 release (L. Shi et al, 2022 ; Zhu et al, 2023 ). The increasing serum LPS, TNF- α , MCP-1 and IL-6 levels mean the low-grade systemic inflammation in MetS rats.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibiting the expression of related inflammatory factors by blocking the TLR4 signaling pathway may have a preventive effect on metabolic diseases [17][18][19]. Obesity-induced inflammation is mainly activated by the TLR4 signaling pathway, which in turn activates the downstream pathway nuclear factor kappa B (NF-κB) and causes the production of pro-inflammatory factor TNF-α, further aggravating the inflammation [20,21]. Studies have demonstrated that TLR4 deficiency can alleviate inflammation and insulin resistance in adipose tissue, and inhibit liver steatosis [22].…”
Section: Introductionmentioning
confidence: 99%